The Development of an Integrated Mechanical Skill Instructional Model (IMSIM) in the Secondary Technology School (STM) for the Improvement of Middle Level Skilled Worker - Riyanto Riyanto (Universitas Negeri Malang, 2016)
This study was conducted to develop an instructional model of mechanical skill learning for the STM students to improve their cognitive, psychomotoric skills, motivation, and creativity. To develop an adequate instructional model, 15 experts were consulted. Based on the result of consultation, the model was revised. The revised model was then tried-out to 20 students of the STM Bengkulu and 17 students of the STM Curup. The result of try-out showed that the developed test items had moderate validity and reliability. The revised instructional model was applied to 25 students of the STM Bengkulu and 30 students of the STM Curup. The result of the study showed that the integrated instructional model was effective to teach mechanical skill, highly effective to increase students' motivation, and moderate to develop creativity